Employees, heads and owners of the company -about need of intra firm training (Путеводитель предпринимателя)
In article various aspects of relevance of intra corporate training programs from a position of staff of the company, heads of an average and the top management and owners are considered. Features of functioning of corporate educational systems, including such new form, as corporate university are marked out.